Perlindungan Konsumen Dalam Transaksi Dagang Melalui Sistem Elektronik - Raflyanto, Muhammad Zhafran; Apriani, Rani (Peneliti.net, 2024)
The volume of electronic trade transactions in Indonesia is steadily increasing. Given its unique nature involving parties from different jurisdictions without physical interaction, legal safeguards are crucial to provide consumer protection in such cross-border transactions. This article use normative juridical research methodologies to analyze consumer protection in commerce transactions conducted through electronic systems and explores strategies of resolving disputes. The research findings indicate that the effectiveness of consumer protection in electronic commerce transactions is hindered due to the fragmented nature of legislation, necessitating the implementation of additional restrictions. Furthermore, Law no. 8 of 1999 pertaining to Consumer Protection has not effectively addressed consumer protection in electronic commerce transactions as a whole, particularly in situations when the involved parties have distinct legal jurisdictions. Regarding consumer disputes, the parties have the option to resolve the matter by either court proceedings or out-of-court settlement, as agreed upon. However, it is also possible to fully utilize online dispute resolution options. This study proposes that the government promptly establish a Government Regulation on commerce transactions conducted through electronic systems and implement regulations for resolving disputes online.